Cationic Surface Modification of PLG Nanoparticles Offers Sustained Gene Delivery to Pulmonary Epithelial Cells - BAOUM, ABDULGADER (2010)
Biodegradable polymeric nanoparticles are currently being explored as a nonviral gene delivery system; however, many obstacles impede the translation of these nanomaterials. For example, nanoparticles delivered systemically are inherently prone to adsorbing serum proteins and agglomerating as a result of their large surface/volume ratio. What is desired is a simple procedure to prepare nanoparticles that may be delivered locally and exhibit minimal toxicity while improving entry into cells for effectively delivering DNA. The objective of this study was to optimize the formulation of poly(D,L-lactide-co-glycolide) (PLG) nanoparticles for gene delivery performance to a model of the pulmonary epithelium. Using a simple solvent diffusion technique, the chemistry of the particle surface was varied by using different coating materials that adsorb to the particle surface during formation. A variety of cationic coating materials were studied and compared to more conventional surfactants used for PLG nanoparticle fabrication. Nanoparticles (~200 nm) efficiently encapsulated plasmids encoding for luciferase (80–90%) and slowly released the same for 2 weeks. In A549 alveolar lung epithelial cells, high levels of gene expression appeared at day 5 for certain positively charged PLG particles and gene expression was maintained for at least 2 weeks. In contrast, PEI gene expression ended at day 5. PLG particles were also significantly less cytotoxic than PEI suggesting the use of these vehicles for localized, sustained gene delivery to the pulmonary epithelium.